ANALYSIS OF LOCALIZED LIMB LOADS FOR INJURY RISK DURING RETURN TO RUNNING PROTOCOLS FOLLOWING ACL RECONSTRUCTION - Taylor, Kendall (East Carolina University, 2017)
Introduction: Running is a typical goal after anterior cruciate ligament reconstruction (ACLR). Return to running (RTR) protocols are intended to provide a safe, incremental exposure to mechanical loads associated with running but none have been evaluated using existing injury prediction thresholds. Additionally, the influence of daily physical activity (PA) level and adherence to RTR protocol guidelines on predicted injury risk is unknown. Objectives: The purpose of this study was to estimate patellofemoral joint (PFJ), tibiofemoral joint (TFJ), and Achilles tendon (AT) injury risk associated with participation in three different RTR protocols as a function of overall daily PA level and protocol adherence. Methods: Average PFJ, TFJ, and AT force impulse/step during walking and running among 38 people with a history of ACLR were used to estimate cumulative impulse data at each site for each day for three RTR protocols. These RTR protocol impulse estimates were summed with the cumulative impulse at each site at progressively greater daily PA levels and input into two published injury prediction equations, the acute:chronic workload ratio (AC ratio) and percent change in daily load. A clinical scenario of nonadherence was evaluated by one week of no running followed by one week of doubling the mileage required in the protocol. Results: Assuming adherence, the AC ratio was below predicted injury risk thresholds at all sites, regardless of PA level (Figure 1A). However, the percent change injury model predicted increased PFJ injury risk when daily PA levels were less than 3,400 steps/day (Figure 1B). The RTR nonadherence model resulted in an AC ratio exceeding injury risk thresholds with PA levels below 2,300, 2,700, and 7,700 steps/day for the AT, TFJ, and PFJ, respectively, while the percent change model predicted increased injury risk at all sites regardless of PA level. The PFJ was at greatest risk for injury in each RTR protocol, regardless of adherence or daily PA level. Conclusions: The results of this study provide a basis for PA and protocol adherence recommendations and insight to the etiology of injuries associated with RTR after ACLR.
Keywords: ACLR; Return to Run; Injury Risk